Hydrophobic Polycationic Coatings Disinfect Poliovirus and Rotavirus Solutions - Larson, Alyssa M. (2010)
Coating surfaces with N-alkylated polyethylenimines (PEIs), namely branched N,N-hexyl,methyl-PEI via covalent attachment to glass or linear N,N-dodecyl,methyl-PEI by physical deposition (“painting”) onto polyethylene, enables the resultant materials to quickly and efficiently disinfect aqueous solutions of (non-enveloped) poliovirus and rotavirus.